Use of electronic educational resources for the development of digital competencies of commerce students - Miloradov, Konstantin; Eidlina, Galina; Sorokina, Marina Yuryevna; Mangusheva, Lyaylya Sayyarovna (Revista EntreLinguas, 2021)
The article examines approaches to the development of digital competencies of commerce students, in the context of increasing requirements for the level of training of specialists from the labor market. A study of the directions of digital transformation in the field of trade, corporate systems for automating business processes of trade enterprises, the requirements of employers, and Russian and foreign experience in training specialists in the field of trade has been carried out. The authors have developed electronic educational resources that are used in the educational process to improve the quality of training specialists in the field of trade. Keywords: digital technologies, digital competencies, university, online learning, trade.